New materialism: An end to certainty - Marn, Travis; Cleave, Jessica Van (Theory and Philosophy in Qualitative Research Methods: Key Concepts, 2026)
The purpose of this entry is to provide an orientation to new materialism, a form of inquiry or philosophy that brings renewed interest to materiality. New materialist philosophies offer an end to certainty, an end to the belief that meaning, knowledge, and agency are fixed and stable. New materialism, however, is not a cohesive body of work but rather a collection of theories, theorists, works, and assumptions, each with its own goals, methods, and desired end points. What constitutes new materialism, what contributes to new materialism, and what inspires new materialist scholarship are not necessarily the same. We trace some of the historical influences of new materialism, highlighting key theories and theorists, describing the intersecting philosophical traditions that mutually constitute new materialism, and exploring the implications of new materialism both for social justice and for qualitative research. © 2026 selection and editorial matter, Aaron M. Kuntz; individual chapters, the contributors.
Keywords: dept.cur

A phenomenological study of the racial sensemaking of Chinese international doctoral students in the United States during and post the COVID-19 pandemic - Wang, Peiwen (International Journal of Qualitative Studies in Education, 2025)
Keywords: China; Ethnography; Interpretative phenomenological analysis; Pandemic; Phenomenology (philosophy); Qualitative research; Racism; Semi-structured interview; Sensemaking; dept.cur

Disconnected in a connected world: improving digital literacies instruction to reconnect with each other, ideas, and texts - Marangell, Joseph; Randall, Régine (Education Sciences, 2025)
This commentary addresses a problem of practice related to student disengagement in technology-rich classrooms, where learners are digitally connected but socially and academically disconnected. Although not an empirical study, the commentary draws on instructional examples from secondary- and graduate-level teaching. The authors examine how digital literacy instruction can strengthen engagement, reading comprehension, and ethical participation in online environments. The article highlights strategies such as the workshop model, multimodal composition, digital content curation, and the use of mentor texts to support critical thinking and collaborative learning. These practices aim to develop students’ analytical skills, awareness of audience, and recognition of their own positionality in digital spaces. Across courses, the authors reflected on increased student engagement when digital tools were used not simply for task completion but to support inquiry, discourse, and authentic creation for real audiences.
Keywords: Comprehension; Computer science; Critical thinking; Digital literacy; Disengagement theory; Linguistics; Literacy; Mathematics education; Pedagogy; Psychology; Reading (process); Reading comprehension; Sociology; Student engagement; Task (project management); dept.cur

“I’m like white people here”: Chinese international doctoral students’ perception of ethno-racial issues in China (poster 23) - Wang, Peiwen (AERA 2025 Annual Conference, 2025)
Keywords: China; Law; Media studies; Perception; Political science; Psychology; Sociology; White (mutation); dept.cur

The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

Producing Participants: Trustworthiness as Convenient Fiction - Van Cleave, Jessica; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Objectivity (philosophy); Qualitative research; Quality (philosophy); Reputation; Rigour; Transparency (behavior); Trustworthiness; Verisimilitude; dept.cur; fiction; methodologies; qualitative criteria; qualitative research; transparency; trustworthiness

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed

Elementary preservice teachers' use of the crosscutting concepts to plan NGSS ‐aligned science lessons in explicit versus non‐explicit contexts - Sherwood, Carrie‐Anne; Benedict‐Chambers, Amanda (School Science and Mathematics, 2025)
Keywords: Context (archaeology); Discipline; Lesson plan; Mathematics; Mathematics education; Next Generation Science Standards; Pedagogy; Plan (archaeology); Psychology; Science education; Significant difference; Sociology; dept.cur; peer-reviewed

Legal Study of Children with Emotional disturbance and Mental Health Needs and Implication for Practice - Dieterich, Cynthia A.; Snyder, Nicole D.; Villani, Christine J. (Journal of Law & Education, 2016)
Keywords: dept.cur; peer-reviewed

Online Research and Media Skills: An instructional model to support students as they search and shift online informational text - O'Byrne, W. Ian; McVerry, J. Gregory (Using Technology to Enhance Reading: Innovative Approaches to Literacy Instruction, 2015)
Enhance students' reading abilities with technology. Discover how technological resources can improve the effectiveness and breadth of reading instruction to build student knowledge. Read real-world accounts from literacy experts, and learn how their methods can be adapted for your classroom. Explore how to foster improvement in student learning using a variety of tools, including interactive whiteboards, tablets, and social media applications. Benefits:Gain insight into ways to incorporate technology into reading instruction.Obtain guidance on choosing progress-monitoring tools to best address your students' needs. Discover strategies to engage students in vocabulary instruction, and help students interpret informational texts. Learn how to use various tools to spark group discussions about literature. Determine how to continually assess students' connections with the assigned reading material. Contents: Part I: Reading Foundations Chapter 1: Foundational Reading Competencies Supported With Technology: Phonemic Awareness and Word Recognition Chapter 2: Rethinking Foundational Reading Skills: Making Room for the Complexities of Digital Texts Chapter 3: Using Tablets to Teach Foundational Skills: Matching Apps to Student NeedsPart II: Reading Fluency Chapter 4: Podcasts: Adding Power and New Possibilities to the Readers Theater Experience Chapter 5: Student-Produced Movies as Authentic Reading Fluency Instruction Chapter 6: Audio-Assisted Reading Builds Reading FluencyPart III: Reading Vocabulary Chapter 7: Post-Reading Vocabulary Development Through VSSPlus Chapter 8: Bringing Words to Life Through Student-Created Vocabulary Videos Chapter 9: Self-Regulated Vocabulary Learning on the InternetPart IV: Comprehension of Informational Texts Chapter 10: Using the Multimodal Explanatory Composition Strategy to Respond to Informational Texts Chapter 11: Annotation Apps: Supporting Middle School Students' Interpretation of Science Texts Chapter 12: Online Research and Media Skills: An Instructional Model for Online Informational TextsPart V: Comprehension of Literary Texts Chapter 13: Digging Deeper With Reader Response: Using Digital Tools to Support Comprehension of Literary Texts in Online Learning Environments Chapter 14: Coding and Connecting Complex Literature Chapter 15: Linking Through Literature: Exploring Complex Texts Through Hypertext Literary AnalysisPart VI: Reading Across Disciplines Chapter 16: Classroom Blogging to Develop Disciplinary Literacy Chapter 17: Using eReaders to Enhance Literacy Instruction in the Content Areas Chapter 18: Supporting Inquiry With Digital Texts in School DisciplinesPart VII: Motivation for Reading Chapter 19: "I Wanted to Film, So I Read the Book": Filmmaking in the English Classroom Chapter 20: eBooks and eReaders: Removing Obstacles, Improving Motivation Chapter 21: Using Literacy iPad Apps for Reading MotivationPart VIII: Reading Assessment Chapter 22: Literacy Assessments in the Digital Age Chapter 23: Developing and Assessing Fluency Through Web 2.0 Digital Tools Chapter 24: Using Blogs as Formative Assessment of Reading Comprehension
Keywords: dept.cur

Implicit Attitudes of International and American Adult Students toward Black and White Teachers - Na, Eunkyung; Tan, Tony X.; Marn, Travis; Ramirez, Rica (Commission for International Adult Education, 2015)
The purpose of this study was to examine hidden prejudice in two groups of adult students, international and American, against black compared to white teachers. Social desirability in the minds of participants may affect the result of a study involving racial bias (Mullins, 1982). For this reason, the researchers created a computer protocol using the standard Implicit Association Test (IAT) to measure the implicit attitudes of participants. The IAT relies on the idea of automatic information process within the mind that is not impacted by social desirability. A clear concern in education is that the racial bias toward minority students will let those implicit biases affect the way they teach those students, creating a self-fulfilling prophesy of poor student performance. But the implicit bias can work both ways and can impact a teacher's effectiveness. Traditional racial prejudice theories usually looked at white's attitudes toward blacks and other groups. This study had a significant directional shift by focusing on the international students' racial attitudes toward black and white teachers. The implicit racial attitudes of international students were also compared to those of American students. The result and evaluation of this study may be a valuable tool to improve student services and teacher professional development in higher education. Suggestions for future research are also provided.[For full proceedings, see ED570489.]
ERIC Number: ED570505
Keywords: Adult Students; African American Teachers; Attitude Measures; College Students; Comparative Analysis; Foreign Students; Gender Differences; Racial Attitudes; Racial Bias; Social Desirability; Statistical Analysis; Student Attitudes; Surveys; Whites; dept.cur

Biracial Place Walkers on Campus: A Trioethnography of Culture, Climate, and Currere - Agosto, Vonzell; Marn, Travis; Ramirez, Rica (International Review of Qualitative Research, 2015)
Send this e-mail to Rica and Travis: Rica and Travis, I wish you could have been at the duoethnography panel. The first presentation had some uneasy conversations. The second, Dr. Colomer's presentation, was cool: A performance with guest actors had some sad moments with death, health issues, and attrition. The next presentation was about miscarriage and grief counseling. I wondered if our paper is frivolous in comparison to the others. I think not. Our episodes of cultural starvation and indifference are there and painful, but our comebacks are so quick (nourishment as resistance), and therefore so is the celebration. Written by Agosto while flying home after presenting at the 2014 International Congress of Qualitative Inquiry.
Keywords: dept.cur

Adoptive Parents’ Suspicion and Coping With the Possibility of Child Abduction for International Adoption in China - Marn, Travis M.; Tan, Tony Xing (The Family Journal, 2015)
In this study, we investigated (1) whether adoptive parents suspected their children might have been victims of abduction for adoption in China and (2) for parents who were uncertain if their own children might be victims of child abduction for adoption, how they coped with the possibility. A total of 342 adoptive parents (representing 529 adopted Chinese children) completed an anonymous online survey on their experiences. Of the 342 parents, 154 (45%) described how they coped with the possibility that their children might be the victims of child abduction for adoption. In terms of suspicion, we found that for about 70% of the children, the parents responded Never; for 18.5% of the children, the parents responded Rarely; for 11.7% of the children, the parents responded Sometimes; and for about 1% of the children, the parents responded that they Always suspected that their children might be victims of abduction for adoption. In terms of coping with the possibility that their children might have been victims of child abduction for adoption, thematic analysis on the 154 parents’ descriptions revealed that parents experienced one or more of seven emotional reactions: sadness, frustration/helplessness, complicity/guilt, anger, fear/worry, hypervigilance, resolve, as well as the belief that they were not affected. Finally, we discussed contributing factors to child abduction for adoption and to adoptive parents’ suspicion of such a practice.
Keywords: dept.cur

Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

Work/Think/Play/Birth/Death/Terror/Qualitative/Research - Wolgemuth, Jennifer R.; Rautio, Pauliina; Koro-Ljungberg, Mirka; Marn, Travis M.; Nordstrom, Susan; Clark, Adam (Qualitative Inquiry, 2018)
Inspired by work/think/play in qualitative research, we centered the idea of “play” in a qualitative research project to explore what proceeding from the idea of work/think/play might look like and accomplish. We pursued play in an experimental qualitative inquiry over dinner one night at the 2016 Annual Meeting of the American Educational Research Association. Our article centers on one work/think/play inquiry three of us conducted. Through a playful account of how play unfolded in our work/think/play inquiry that evening, we explore research play as generative, deadly, and censored in the context of neoliberalism and other terrors. We reflect on what (good) play does in qualitative research, what our work/think/play/birth/death/terror/qualitative/research accomplished, if anything. Maybe research play is vital, what keeps us fit to do critical qualitative research. Yet research play moves (well) beyond normative rules of much qualitative research. Is it worth the risk? Can we know? Even after?
Keywords: dept.cur

Creating a Space for Teacher Candidates Committeed to Urban Settings: Action Research Program on the Urban Education Fellows Program - Bower-Phipps, Laura; Marx, H. A. (Teacher Education Yearbook XXIV: Establishing a Sense of Place for All Learners in 21st Century Classrooms and Schools, 2015)
The Association of Teacher Educators (ATE) Yearbook XXIV offers 16 captivating chapters related to establishing a sense of place or belonging for P-12 students, classroom teachers, teacher candidates, and teacher educators. The chapters include theory, research, concepts, principles, practices, and programs that inform and support as well as question and challenge readers from multiple perspectives. Readers gain insights and inspiration that illustrate ways teachers and learners negotiate meaning in environments where everyone experiences social and cultural connections with personal and academic fulfillment. Collectively, the authors identify, describe, analyze, and advance issues associated with creating both an individual and a shared sense of place among the ever-changing populations in contemporary P-12 schools and classrooms. Like human geographers, teacher educators and educational researchers study environments where children grow up and create bonds with their early environments that continue to influence them throughout their lives based on the ways in which meaning is negotiated in that early space. Candidates, teachers, and teacher educators benefit by investigating the presence and power of these landscapes impacting the teaching, learning, and schooling.
Google-Books-ID: 4bodCwAAQBAJ
Keywords: Education / Administration / General; Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Learning Styles; Education / Student Life & Student Affairs; dept.cur

Developing as Teachers and as Researchers: Emerging Professionals' Experiences with Cooperative Inquiry - Bower-Phipps, Laura; Cruz, Maria; Albaladejo, Cristina; Johnson, Arlette; Homa, Thomas (Networks: An Online Journal for Teacher Research, 2016)
This article details the second cycle of cooperative inquiry undertaken by emerging educators who self-identify as "other" because of gender, language, ethnicity, and/or sexual orientation. The current cycle focuses on the impact participation in cooperative inquiry had on researchers' teaching practices. Data sources include transcripts of group discussions and reflective writing completed six months, eighteen months, and two years after the completion of the first cycle of cooperative inquiry. Findings suggest that as a result of engagement in cooperative inquiry, the teacher/researchers established practices to decrease isolation, build unity, and understand students' backgrounds. Teacher/researchers viewed themselves as advocates for diversity within the classroom, took a collaborative approach to teaching, and came to see research as an essential element of effective teaching.
ERIC Number: EJ1152312
Keywords: Beginning Teachers; Cooperation; Educational Practices; Elementary School Teachers; Inquiry; Minority Group Teachers; Preservice Teachers; Self Concept; Social Distance; Student Teachers; Teacher Educators; Teacher Researchers; dept.cur

Academic bullying as a racialized phenomenon in STEM higher education: Centering the experiences of Asian international doctoral students - Wang, Peiwen (Journal of International Students, 2024)
While students of color’s experiences of academic bullying from their advisors have been documented in the literature (e.g., Moss & Mahmoudi, 2021), little is known regarding the role that race plays in the normalization and perpetuation of academic bullying within higher education. Utilizing Asian critical theory (AsianCrit) as both the theoretical and analytical lens, this phenomenological study centers five STEM Asian international doctoral students’ experiences of academic bullying through semi-structured interviews. It is found that racialized academic bullying is operationalized by a) legitimizing exploitation through racializing discourses; b) maintaining White supremacy across transnational contexts; and c) intersecting systems of oppression. Implications and recommendations are offered as to what stakeholders can do collectively to address racialized academic bullying towards minoritized students and to combat systemic inequities and oppression.
Number: 4
Keywords: STEM; dept.cur; peer-reviewed

Planning for Equitable Student Sensemaking: An Examination of Preservice Teachers Noticing of Elementary Science Lesson Plans - Benedict-Chambers, A.; Sherwood, C.-A. (Journal of Science Teacher Education, 2024)
Designing and analyzing lesson plans is a ubiquitous practice in teacher education, and yet we know little about how preservice teachers (PSTs) notice elements of their lesson plans that afford opportunities for supporting equitable student sensemaking. We investigate how the use of a tool, a framework for supporting equitable sensemaking, guided 36 PSTs to notice four features of equitable sensemaking in their plans. Qualitative analysis of PSTs’ comments about their plans generated a coding rubric and three associated levels for noticing. These levels included (1) paying little to no attention to explicit strategies and making assumptions about the ways that traditional classroom practices might facilitate equitable sensemaking; (2) attending to some strategies but providing few details; and (3) attending to and making connections between specific moves and broader principles and practices of supporting equitable student sensemaking. Guided by the tool, PSTs were able to provide elaborate details about their plans to design instruction to engage students in authentic scientific work focused on investigating and explaining phenomenon (feature 4) and to position students as knowers (feature 2), but they struggled to discuss explicit ways to leverage students’ lived experiences in their science lessons (feature 3) and facilitate equitable engagement and participation (feature 1). This suggests that even with the use of a tool, it may be challenging for PSTs to attend to and describe in detail strategies for leveraging students’ out-of-school lives and interests for science learning and explicit classroom strategies for making learning accessible and engaging for all. © 2024 Association for Science Teacher Education.
Keywords: Equitable science instruction; dept.cur; methods courses; noticing; peer-reviewed; preservice teachers

Proverb: Nearly Spring in a New Hampshire Barn - Randall, Regine (On and Off the Road: Poems of New Hampshire, 2020)
"This poetry anthology, with poems from poets throughout New England and from other states - is a result of Peterborough Poetry Project's second poetry contest. We invited poets, writers, and observers to submit up to three poems about New Hampshire - past, present, future, or fantasy. Forty-eight poems from the contest form this book. The poems are in three different sections by themes: People, Places, and The Wild, but readers may find that several poems have more than one theme. A poem may appear to be about nature, but also our reactions to it. Another poem may appear to be true, but might be pure fantasy. Such is the nature of poetry: read it for the obvious, then read it again to see if more reveals itself"–Back cover
Google-Books-ID: 9QSYzQEACAAJ
Keywords: dept.cur; literary-poetry

New Literacies of Online Research and Comprehension - Leu, Donald J.; Kiili, Carita; Forzani, Elena; Zawilinski, Lisa; O'Byrne, W. Ian; McVerry, J. Greg (The Encyclopedia of Applied Linguistics, 2021)
This entry explores the question of how to conceptualize literacy as a deictic concept, one that continually changes as new technologies for literacy and learning emerge. It suggests a dual-level conceptualization of theory: a New Literacies theory as an overarching theory that encompasses perspectives and findings from the many studies of literacy, which are referred to as new literacies theories, using lower case. It then focuses special attention on an important lower-case theory, the new literacies of online research and comprehension. This new literacies theory frames online reading as a process of problem-based inquiry involving the new skills, strategies, dispositions, and social practices that take place as we use the Internet to solve problems and answer questions. Current understanding of online reading to learn from a New Literacies perspective is informed by recent research using assessments that measure students' ability to conduct online research in science and comprehend what they read in a virtual online world. Findings suggest that online reading requires different skills than reading paper materials; that differences across modes of reading are important for school learning; and that the Internet is best conceived as a literacy issue rather than a technology issue.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781405198431.wbeal0865.pub2
Keywords: Literacy; Literacy Practices Online; New Literacies; Online Reading; Teaching Reading; dept.cur

New Literacies of Online Reading Comprehension - Leu, Donald J.; Everett-Cacopardo, Heidi; Zawilinski, Lisa; McVerry, Greg; O'Byrne, W. Ian (The Encyclopedia of Applied Linguistics, 2012)
Literacy has become deictic (Leu, 2000); the meaning of literacy is rapidly changing as new technologies for literacy continually appear and new social practices of literacy quickly emerge.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781405198431.wbeal0865
Keywords: Internet; dept.cur; language in the classroom; literacy; online reading comprehension; reading

The personal is professional: Unpacking cultural sanctions through the identities of mother /educator/lesbians - Bower-Phipps, Laura (Sexual Orientation and Teacher Identity: Professionalism and LGBTQ Politics in Teacher Preparation and Practice, 2019)
Keywords: dept.cur; dept.eng

Extending Student (R)esponse to (E)ngagement in a Bilingual Classroom: An Analysis of Identity-Infused Classroom Discourse - Ferraro, Marisa (Empowering Students Through Multilingual and Content Discourse, 2023)
The growing diversity of students in schools has raised important questions regarding how students learning English and discipline-content simultaneously succeed academically. This challenge has been exacerbated by disparities in resources among multilingual communities throughout the COVID-19 pande...
Keywords: dept.cur

Cultivating Language and Identity through Multimodal Literacies: Back to the StoryBoard - Ferraro, Marisa; Mendoza, Kristin Bengtson (Multimodal Literacies in Young Emergent Bilinguals: Beyond Print-Centric Practices, 2022)
Keywords: dept.cur

Axes of support: Explicit to implicit and practical to epistemic - Fick, S.J.; Arias, A.M.; Vo, T.; Sherwood, C.-A.; Benedict-Chambers, A.; Lo, A.S. (Comput. -Supported Collab. Learn. Conf., CSCL, 2020)
Drawing from analyses of teaching and learning, we posit a theoretical framework of axes, practical to epistemic and explicit to implicit, which frame four quadrants of support needed to know how and why to use the crosscutting concepts in sensemaking. This work has implications for the design of learning environments that use the crosscutting concepts in scientific sensemaking. © ISLS.
Journal Abbreviation: Comput. -Supported Collab. Learn. Conf., CSCL
Keywords: Computer aided instruction; Four quadrant; Learning environments; Sensemaking; Teaching and learning; Technology transfer; Theoretical framework; dept.cur

Applied qualitative data analysis after the ontological turn - Marn, T.M.; Wolgemuth, J.R. (Qualitative Report, 2021)
In this article we demonstrate the use and usefulness of new materialism as an analytic lens in applied qualitative inquiry. Intended as a possible entry point to applied inquiry after the ontological turn, we draw on Barad's agential realism to analyze three existing transcripts of focus groups conducted with healthcare workers, traditional birth attendants, and mothers to explore the postnatal care referral behavior of traditional birth attendants in Nigeria. We describe elements of our data analysis process including deep reading, summoning of the inquiry, delaying the inquiry, attuning to glowing data, and writing. We explore how the research phenomenon enacted agential cuts that distinguished participants (healthcare workers, traditional birth attendants, and mothers) and relayed their participation in the focus group. We show how the inclusion of the mothers' babies and the transcripts themselves made available some understandings at the possible exclusion of others. Our Baradian, new materialist analysis shows the inextricability of interview materials (things) and language (discourse) and demonstrates that all applied research is bounded and affected by its material conditions. As a point of entry, we hope our illustration sensitizes applied qualitative researchers to how research decisions, research materials, and research cultures produce what can be known and lived within and beyond the research encounter. © 2021 Nova Southeastern University. All rights reserved.
1 citations (Crossref) [2023-10-31] tex.author_keywords: Agential realism; New materialism; Post-qualitative inquiry; Qualitative data analysis tex.document_type: Article tex.source: Scopus
Keywords: dept.cur; peer-reviewed

From Leaders to Accomplices: Autoethnography as Praxis in Teacher Education - Powell, Jessica (Re-Imagining Transformative Leadership in Teacher Education, 2021)
This is the third and final book in the series Transformative Pedagogies in Teacher Education. Like the first two books in the series it is geared towards practitioners in the field of teacher education. This third book focuses on transformative leadership in teacher education. In other words, the kind of leadership and practices that will be important and necessary to bring about the kind of changes that both teachers and students seek to improve educational outcomes for all students, but in particular Black, Indigenous and racialized students who have been traditionally underserved by the education system. Teacher leadership plays an important role in transformative educational change that challenges all forms of oppression and white supremacy. This book features chapters by a collection of scholars, teacher educators, researchers, teacher advocates and practitioners drawing on their research and experiences to explore critical issues in teacher education. The book will be useful to teacher educators working with teacher candidates in different contexts, experienced teachers and school leaders. Given demographic shifts and the need for educators to respond to growing diversity in schools, educators will find valuable strategies in Transformative Pedagogies in Teacher Education: Re-Imagining Transformative Leadership in Teacher Education they can employ in their own practice. In addition to valuable strategies, authors explore different approaches and perspectives critical in these changing and challenging times. Critical notions of education are posited from different perspectives and contexts. This book will be useful for teacher education programs, principal preparation programs, in-service teachers, school boards and districts engaging in ongoing professional development of teachers and school leaders.
Google-Books-ID: moc4EAAAQBAJ
Keywords: Education / Leadership; Education / Professional Development; Education / Teaching Methods & Materials / Social Science; dept.cur

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
2 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
tex.ids: sinclairBecomingAlliesAccomplices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084794698 type: Article
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Lesbian mothers' bids for normalcy in their children's schools - Bower, Laura A; Klecka, Cari L (The Educational Forum, 2009)
Albeit growing in number, lesbian mothers and their children remain a statistical minority in schools. Lesbian mothers in this study described their families as “normal” or “just like any other family.” From the perspective of queer theory, normal is a socially constructed and insidious concept. This study analyzes both the strategies participants used to be recognized as normal in their children’s schools and the reasons such recognition was perceived to be important by participants. © 2009 Taylor & Francis Group, LLC.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-920-664-272-132 tex.type: [object Object]
Keywords: dept.cur

(Re)Considering normal: queering social norms for parents and teachers. - Bower, Laura A; Klecka, Cari L (Teaching Education, 2009)
Recent debates regarding same-sex marriage and gay and lesbian adoption highlight the role of schools as sociopolitical institutions. Accordingly, teachers operating within social norms have considerable influence through their interactions with students and their families. Previous research points to lesbian, gay, bisexual, and transgender (LGBT) parents' frustrations with their children's schools, particularly as teachers resist representing LGBT families within curricula and fail to intervene when homophobic comments are made. Yet teachers' capacity to embrace diverse family structures while adhering to cultural expectations for teachers remains unexplored. This study, rooted in queer theory, explores the social norms teachers name for parenting in school settings and the way teachers position LGBT parents within these norms. Findings point to social norms for teachers and parents which indicate that teachers operate within heteronormative frameworks. They consider heterosexuality to be normal, while positioning LGBT identities as deviant. This is troubling given documented connections between teacher attitudes and parental involvement and between parental involvement and student achievement. Unchecked, heteronormative practices may result in inequitable school experiences for LGBT parents and their children. Teacher education must minimize heteronormativity through equipping teachers to attend to their own notions and assumptions regarding the intersection of parenting and sexual orientation. © 2009 Taylor & Francis.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-813-151-713-833 tex.type: [object Object]
Keywords: Teacher socialization; Teacher thinking and knowledge; dept.cur

The Ecology of Education: Knowledge Systems for Sustainable Development and Sustainability - Wensing, E J; Torre, Carlos Antonio (Journal of Teacher Education for Sustainability, 2009)
The Ecology of Education: Knowledge Systems for Sustainable Development and SustainabilityResearch in knowledge systems for sustainable development (KSSD) seeks to determine how science and technology can be put into effective action at a local level. Teachers in education for sustainability attempt to achieve the same goal. KSSD research has indicated that success is context driven, that panaceas are inappropriate and that knowledge systems at best provide solutions in evolution. In this paper, we describe a teaching framework that we are developing to support KSSD researchers and teachers in education for sustainability based in ecology of education. While a need for ecology in education may be apparent, there is concurrently an equally important need for ecology of education. We argue that one cannot teach ecology in education adequately without an appropriate ecology of education. This paper first explains why teachers need to know this and then describes how teachers of education for sustainability can implement and assess this approach in the classroom.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-112-898-576-37X tex.type: [object Object]
Keywords: dept.cur

Responding to Heteronormativity: Lesbian, Gay, Bisexual and Asexual Preservice Teachers’ Dreams and Fears - Bower-Phipps, Laura (Current Issues in Education, 2020)
Heteronormativity, the “privileging of heterosexuality through its normalization” (Jackson, 2006, p. 109), causes confusion and anxiety for many lesbian, gay, bisexual, and asexual preservice teachers as they consider how they will talk about their lives with students. This article explores how preservice teachers have experienced the normalization of heterosexuality and the ways in which these experiences will shape their professional practices. Focus group and follow up interviews with lesbian, gay, bisexual, and asexual preservice teachers were analyzed using a constant comparison method. Findings suggest that participants’ professional vision was largely a response to heteronormativity. They wanted to be out, be role models, and create safe spaces; yet they felt unable to achieve this vision in what they perceived as heteronormative school climates. Implications for teacher preparation programs and policies include the importance of equipping all preservice teachers to identify and disrupt heteronormativity in schools.
Number: 1
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

“The Goals Remain Elusive”: Using Drawings to Examine Shifts in Teachers’ Mental Models Before and After an NGSS Professional Learning Experience - Sherwood, Carrie-Anne (Journal of Science Teacher Education, 2020)
Teachers’ ability to effectively enact the ambitious vision of the NGSS depends on their understanding of the conceptual and instructional shifts required, and their interpretation of how to implement these shifts in their classrooms. Thus, understanding teachers’ practical knowledge regarding the shifts is an important step in supporting them to effectively implement the NGSS vision. This study used a mental models framework and teacher drawings to examine the practical knowledge of 22 in-service secondary science teachers before and after professional development that was designed to support them to understand and make incremental instructional shifts aligned with the NGSS. Findings indicate that teachers’ mental models shifted in two promising ways. First, teachers recognized that their roles and their students’ roles would need to change, and second, the doing of science looks and sounds different than what was traditionally done in their classrooms. However, findings also suggest that teachers struggled to reconcile new ideas from the PD with their previous mental models of their classroom practice. These findings are significant because they indicate, teachers may have more fully-formed mental models for what science teaching and learning looks and sounds like when it is focused on what most would traditionally think of as classroom science doing (e.g., “doing labs”), or when it includes traditional knowledge dissemination structures (e.g., lectures). This has important implications for science teacher educators and researchers, which will be discussed. © 2020, © 2020 Association for Science Teacher Education.
2 citations (Crossref) [2023-10-31] tex.ids: sherwoodGoalsRemainElusive2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088064339 type: Article
Keywords: NGSS; Science teacher education; dept.cur; mental models; peer-reviewed; professional development; teacher drawings; teacher practical knowledge

Developing mentors: an analysis of shared mentoring practices - Bower-Phipps, Laura; Klecka, Cari Van Senus; Sature, Amanda L (The New Educator, 2016)
Understanding how experienced teachers share and articulate effective mentoring practices can guide efforts to prepare quality mentors. This qualitative study focused on mentoring practices within a teacher-designed student-teaching program conceptualized while the mentor teachers within the program were students in a graduate-level mentoring course and implemented upon the mentors’ completion of their graduate studies. Data sources included interviews and field notes from meetings with mentors and student teachers. The results detail specific mentoring practices: explicit instruction through scaffolding, developing the whole teacher, student-teacher-directed learning, fostering student teachers’ individual practice, explicit mentoring of one another, and reflecting on mentoring. These practices were enabled by program structures such as mentor meetings, an online forum, and mentors’ observation of all student teachers in the program. © 2016, © 2016 CCNY and ATE.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-875-982-659-553 tex.type: [object Object]
Keywords: dept.cur; peer-reviewed

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
1 citations (Crossref) [2023-10-31] tex.eissn: 1936-2706 tex.unique-id: ISI:000363658800011 Citation Key Alias: ISI:000363658800007
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features

Guiding students as they explore, build, and connect online - McVerry, J. Gregory; Belshaw, Doug; O'Byrne, W. Ian (Journal of Adolescent & Adult Literacy, 2015)
5 citations (Crossref) [2023-10-31] tex.eissn: 1936-2706 tex.unique-id: ISI:000353969000003
Keywords: dept.cur

Improving students' academic learning by helping them access text - Ben-Avie, Michael; Randall, Régine; Dunne, Diane Weaver; Kelly, Chris (Recent Advances in Assistive Technologies to Support Children with Developmental Disorders, 2015)
Conventional methods of addressing the needs of students with print disabilities include text-to-speech services. One major drawback of text-to-speech technologies is that computerized speech simply articulates the same words in a text whereas human voice can convey emotions such as excitement, sadness, fear, or joy. Audiobooks have human narration, but are designed for entertainment and not for teaching word identification, fluency, vocabulary, and comprehension to students. This chapter focuses on the 3-year pilot of CRISKids; all CRIS recordings feature human narration. The pilot demonstrated that students who feel competent in their reading and class work tend to be more engaged in classroom routines, spend more time on task and demonstrate greater comprehension of written materials. When more demonstrate these behaviors and skills, teachers are better able to provide meaningful instruction, since less time is spent on issues of classroom management and redirection. Thus, CRISKids impacts not only the students with print disabilities, but all of the students in the classroom.
Citation Key Alias: pop00414
Keywords: dept.cur

Multimodal response and writing as poetry experience - Pet, Sue Ringler; Mcverry, J Gregory; Obyrne, W Ian (Exploring Multimodal Composition and Digital Writing, 2014)
What affordances do multimodal and digital information provide to the student and teacher with regard to responding to and writing poetry? This question juxtaposes one of the oldest literary genres in human history (i.e., poetry), with some of the newest technologies available. To enrich the content and effect as students experience poetry, technology may seem like an unwelcome stranger. Research has found, however, that “multimedia texts and multimodal composing may actually shift classroom culture toward a more learner-centered paradigm” (Chandler-Olcott & Mahar, 2003, pp. 381-382). This chapter explores the integration of technology with both response to poetry and authorship of poetic works as a means to enrich English classroom experiences. In the authors’ view, important work in this arena must not use technological tools for the sake of using technology in the classroom, but, rather, for the sake of enriching literary experiences. Ultimately, by connecting response, authorship, and multimodal technologies, the teaching of poetry may be enhanced by the teaching of 21st century literacy skills. Toward these ends, the authors share opportunities for intertwining multimodal text with the teaching of poetry to enrich literacy and literary experience in middle and high school classrooms.
Citation Key Alias: lens.org/010-469-758-942-570
Keywords: dept.cur

Vowel representations in the invented spellings of Spanish-English bilingual kindergartners - Raynolds, Laura B.; Uhry, Joanna K.; Brunner, Jessica (Reading and Writing, 2013)
The study compared the invented spelling of vowels in kindergarten native Spanish speaking children with that of English monolinguals. It examined whether, after receiving phonics instruction for short vowels, the spelling of native Spanish-speaking kindergartners would contain phonological errors that were influenced by their first language. Results showed no differences between the two groups on the number of correct short vowel spellings, even though the sounds for four of the five English short vowels do not exist in Spanish. By contrast, differences were observed in the representation of long vowels with a higher rate of error among ELLs. The students had not received explicit instruction in long vowels. ELLs appeared to be trying to represent the diphthongized nature of some English long vowels by spelling long vowels with more than one vowel. The results support the authors' hypothesis that kindergarten phonics instruction had an impact on the invented spellings of new second language vowel phonemes.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-056-476-891-636 tex.unique-id: [object Object]
Keywords: Bilingual; English language instruction; Invented spelling; Spanish language; dept.cur; peer-reviewed

Everyone has a story: A collaborative inquiry project by five teacher candidates of color and one white professor - Bower-Phipps, Laura; Tate, Rachel Watanabe; Mehta, Sejal; Sature, Amanda L (Current Issues in Education, 2013)
Initiatives to increase the number of teachers of color in U.S. public schools must be accompanied by culturally relevant teacher preparation for candidates of color. This study is a cooperative inquiry (Heron, 1996) conceived, conducted, and analyzed by five preservice teachers of color and one of their professors, a white lesbian. The women met biweekly for a year to co-construct meaning from their experiences in a teacher education program. They analyzed data sources together, including meeting transcripts, autobiographical sketches, and reflective writing on themes from the data. Key findings include the complexity of teacher candidates' identities; the importance of support systems for teacher candidates of color, particularly within predominantly white contexts; the connection between teacher candidates' backgrounds and their visions as teachers; and the role others' perceptions, particularly teacher educators, have played in teacher candidates becoming teachers.
Citation Key Alias: lens.org/033-975-273-700-369 tex.type: [object Object]
Keywords: Cooperative inquiry; Diversity; Teacher identity; Teachers of color; dept.cur; peer-reviewed; ⛔ No DOI found

The new literacies of online reading comprehension: expanding the literacy and learning curriculum - Leu, Donald J.; McVerry, J. Gregory; O'Byrne, W. Ian; Kiili, Carita; Zawilinski, Lisa; Everett-Cacopardo, Heidi; Kennedy, Clint; Forzani, Elena (Journal of Adolescent & Adult Literacy, 2011)
73 citations (Crossref) [2023-10-31] tex.orcid-numbers: Kiili, Carita/0000-0001-9189-4094 tex.unique-id: ISI:000295394000002
Keywords: dept.cur

Surpassing normal: preparing teachers for diverse learners - Bower, Laura A; Sature, Amanda L (Action in teacher education, 2011)
Teacher education must prepare teacher candidates for diverse contexts and diverse learners. Such preparation involves teacher candidates unearthing their assumptions about diverse populations and understanding the roles candidates' own backgrounds play in these assumptions. Queer theory can facilitate this process through attention to culturally constructed notions of “normal” and “deviant.” This chapter investigates a strategy intended to identify teachers' cultural expectations through disrupting candidates' perceptions of “normal” students. Data sources include responses to a specific learning activity, interviews, and demographic surveys. Findings indicate that teacher candidates are reluctant to discuss certain demographic descriptors, such as race/ethnicity and sexual orientation, preferring to focus on students' interests and social behaviors. candidates' conceptions of a “normal” student mirror their own experiences. Interview responses suggest that the learning activity disrupted these conceptions. Implications point to the importance of discussing diversity in teacher education courses and the necessity of fieldwork in diverse contexts. © 2011, Copyright Association of Teacher Educators.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-625-205-447-042 tex.type: [object Object]
Keywords: dept.cur

Braiding teacher practice and class-wide dialogue: An historical inquiry across three sociocultural interventions - Palincsar, Annemarie Sullivan; Marcum, Meredith Baker; Fitzgerald, Miranda; Sherwood, Carrie-Anne (International Journal of Educational Research, 2019)
3 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed

Start here, or here, no here: introductions to rethinking education policy and methodology in a post-truth era - Wolgemuth, Jennifer R.; Koro-Ljungberg, Mirka; Marn, Travis M.; Onwuegbuzie, Anthony J.; Dougherty, Shaun M. (Education Policy Analysis Archives, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations. © 2018, Arizona State University. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00129 tex.type: [object Object]
Keywords: Education policy; Fake news; Methodology; Post-truth; dept.cur; peer-reviewed

Examining the work of “scaffolding” in theory and practice: A case study of 6th graders and their teacher interacting with one another, an ambitious science curriculum, and mobile devices - Palincsar, Annemarie Sullivan; Fitzgerald, Miranda Suzanne; Marcum, Meredith Baker; Sherwood, Carrie-Anne (International Journal of Educational Research, 2018)
This case study features a class of sixth-grade students and their science teacher enacting a curriculum designed to teach the particulate nature of matter and phase changes. The class used a mobile device with several applications that supported reading, writing, viewing, and modeling. We examine the role of the teacher, the device, the peers, and the curriculum itself in scaffolding student learning.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-877-409-652-814, pop00069 tex.type: [object Object]
Keywords: Collaboration; Conceptual understanding; Modeling; Peer-mediated learning; Scaffolding; States of matter; Zones of proximal development; dept.cur; peer-reviewed

Joyfully engaged in multimodal learning - Shaw, Louise J. (Promoting social emotional learning in the classroom: Creativity, connections, and engagement, 2017)
Keywords: dept.cur

It’s all Greek: Ancient history as a community journey - Shaw, Louise J. (Impacting literacy through home and community connections, 2017)
Keywords: dept.cur

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
0 citations (Crossref) [2023-10-31]
Keywords: Common core; Writing; dept.cur; dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000398445600003, lens.org/009-289-778-807-372 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed